Proposing a Relationship-Centered SDM process conceptual model for chronic disability: Presenter(s): Marla Clayman, N/A, United States. (April 2023) - Papadimitriou, Christina; Mallinson, Trudy; Weaver, Jennifer; Guernon, Ann; van der Wees, Philip; Kot, Trish; Ford, Paige
Abstract : Background: Current models of shared decision making (SDM), typically based on a brief outpatient encounter, do not fit well in describing the rehabilitation context for persons who lack cognitive capacity to report their wishes, such as persons with disorders of consciousness, severe dementia, and other disabilities. Rehabilitation involves specialized teams of practitioners (e.g., physical and occupational therapists, speech-language pathologists, rehabilitation nurses), family care partners, and numerous, frequent, small-scale decisions are made in-the-moment (i.e., micro-decisions) within the context of a larger treatment or therapeutic goal. An SDM model is necessary to support rehabilitation practitioners' engagement in the process of SDM with family care partners throughout micro-decisions and larger treatment decisions. Methods: Our clinical experiences with these patient populations, exchanges with care partners and practitioners, and empirical evidence from previous studies underpinned our interest to find an existing SDM process model and adapt it. We thus undertook a literature review of SDM process conceptual models that could be adapted for use in rehabilitation settings. Findings: Iterative analyses of literature reviews and adaptation of Clayman's Narrative, Person-Centered SDM model created a new model explicating SDM processes that align with the complex characteristics and relational nature of SDM for persons who cannot advocate for themselves, their family care partners, and rehabilitation practitioners. This model identifies 7 relational dimensions including: when SDM occurs in one's recovery journey, complexity of decisions, and stakeholder skills and information exchanges that will be used to design relationship-centered assessments. Discussion: Our Relationship-Centered SDM process model is inclusive of all stakeholders engaged in continuing care for patients who cannot advocate for themselves, acknowledges the relational nature of decision-making, and supports the inclusion of micro-decisions. Future work will pilot test the model with empirical evidence.